Torres de vento como estratégia de desempenho térmico na ventilação natural de habitações em lotes mínimos do Planalto Pici, em Fortaleza - Rozzoline Muniz, Lucas Ribeiro (2019)
This research aims to identify and classify architectural strategies that favor natural ventilation based on a comparative analysis of narrow dwellings on the Pici Plateau, in Fortaleza. Architectural projects that seek natural ventilation are particularly important in popular housing, especially in dense urban areas. In Fortaleza, it is common for popular buildings to not present effective bioclimatic strategies as there are basic social factors that are more important in defining spatial needs: family size, limited economic resources and little knowledge about the technical options appropriate to the socio-environmental reality. Technical standards on the thermal performance of buildings, such as NBR 15.220-3 and NBR 15.575, reaffirm the urgency of this issue. This work analyzes the architectural solution of the wind tower by evaluating, through computer simulations, the influence of natural ventilation (convective phenomenon of air masses) on the thermal performance of buildings. The result of the simulations allows, after qualitative and quantitative comparisons, to identify alternatives for better energy, comfort and health performance for homes for the low-income population that do not receive technical support from the City of Fortaleza. This work brings together social, economic processes and ecological logic.